One size may not fit all: Welfare benefits and cost reductions with differentiated household electricity rates in a general equilibrium model - Farhad Daruwala; Frank T. Denton; Dean C. Mountain (McMaster University, Research Institute for Quantitative Studies in Economics and Population (QSEP), 2017)
We consider optional TOU (time-of-use) pricing for residential consumers as an alternative to a single TOU or flat rate structure offered by a publicly regulated electricity supplier. A general equilibrium model is developed and used to explore and quantify the effects of optional pricing on welfare, consumption, and production costs. The model assumes that households can be classified into internally homogeneous groups with differing utility functions, incomes, demand elasticities, and committed consumption requirements. Substitution for electricity among TOU periods and between electricity and other goods is allowed for in the model on the demand side, and differing TOU-specific marginal costs on the supply side. The supplier in the model offers to each household a menu of possible rate sets obtained by maximizing a collective welfare function subject to three types of restriction: Pareto efficiency (no household is worse off under the proposed pricing scheme than under the current pricing scheme); incentive compatibility (every household weakly prefers its set of rates to the sets chosen by other households); breakeven supplier revenue (aggregate revenue must equal aggregate cost). The model is calibrated realistically with three household groups and three distinct TOU costing periods, and used in a series of simulation experiments, including experiments with alternative demand elasticities and marginal cost parameters. The use of optional pricing is shown to increase overall consumer welfare and reduce average production cost. However, the distribution of welfare effects can be uneven, with the highest income group dominating the market to the relative disadvantage of the lowest group. To deal with that situation an alternative strategy with a targeted rate structure for the lowest income group is proposed, corresponding to a modified version of the model specified in which some incentive compatibility restrictions are relaxed. Simulations show that the strategy can be effective in bringing about a more equitable distribution of welfare gains while still maintaining optional TOU pricing.
Keywords: D11; D12; D82; Q41; D58; D61; L94; 330; Optional Differentiated Time-of-Use Rates; Pareto Efficiency; Incentive Compatibility; Welfare Benefits; General Equilibrium; Electricity Utility; Consumer Demand